2009
DOI: 10.3171/2009.2.focus098
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of spinal dural arteriovenous fistulas

Abstract: Object Spinal dural arteriovenous fistulas (DAVFs) are the most common spinal vascular malformations and can be a significant cause of myelopathy, yet remain inefficiently diagnosed lesions. Over the last several decades, the treatment of spinal DAVFs has improved tremendously due to improvements in neuroimaging, microsurgical, and endovascular techniques. The aim of this paper was to review the existing literature regarding the clinical characteristics, classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 58 publications
0
63
0
1
Order By: Relevance
“…The optimal management of SDAVF by initial surgery or embolization remains controversial and a multidisciplinary approach has been suggested [7,16,[18][19][20]. It involves embolization as the initial management tool and surgery if embolization fails or is considered difficult and/or unsafe.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal management of SDAVF by initial surgery or embolization remains controversial and a multidisciplinary approach has been suggested [7,16,[18][19][20]. It involves embolization as the initial management tool and surgery if embolization fails or is considered difficult and/or unsafe.…”
Section: Introductionmentioning
confidence: 99%
“…2,32 A trend has suggested that earlier exclusion of the fistula correlates with improved motor function. 30 In general, studies suggest that bladder function, if affected, does not recover. 6,17,32 In our study improvement in motor function after treatment was more likely to occur than improvement in micturition dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…33 Endovascular embolization is an effective therapy in the treatment of SDAVFs and can be used as a definitive intervention in most patients. 30 The success of endovascular treatment is believed to be dependent on complete occlusion of the proximal radicular draining vein and the site of the fistula itself. The goal of treatment, regardless of the type of intervention, is to eliminate the abnormal arteriovenous communication to avoid progression or worsening of the neurologic symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8,25 Currently, surgical ligation, endovascular embolization, and a multidisciplinary approach are all used for the treatment of spinal DAVFs. 9,30,32,33 Once the diagnosis of a spinal DAVF has been made and the fistula has been successfully closed, a majority of patients, up to 80%-90% in some series, 17 will demonstrate either improvement or stabilization of symptoms, particularly lower-extremity strength. 8,13 Aghakhani et al 2 showed that even patients with complete paraplegia at the time of treatment can demonstrate a significant improvement in function following intervention.…”
Section: Discussionmentioning
confidence: 99%